1996
DOI: 10.3109/10428199609054842
|View full text |Cite
|
Sign up to set email alerts
|

Endogenous Murine Leukemia Virus DNA Sequences in Murine Cell Lines: Implications for Gene Therapy Safety Testing by PCR

Abstract: Safety testing for replication-competent retrovirus (RCR) is an important requirement in gene transfer clinical trials using retroviral vectors. A sensitive polymerase chain reaction (PCR) method is one approach to RCR detection. Only in the presence of RCR will the pol-env encoding sequences, necessary for viral replication and packaging, be amplified from proviral DNA in infected indicator cells. To avoid false-positive results in this assay it is crucial that indicator cell lines are free of endogenous retr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

1998
1998
2009
2009

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…The adherent LTMC cells were harvested by trypsinization and aliquots of cells were used in progenitor and molecular assays of gene transfer. Culture supernatant was tested in a marker rescue assay for replicationcom petent retrovirus (Allan et al, 1996). The remaining cells were either cryopreserved or infused directly.…”
Section: Marrow Cultures and Transduction Smentioning
confidence: 99%
See 1 more Smart Citation
“…The adherent LTMC cells were harvested by trypsinization and aliquots of cells were used in progenitor and molecular assays of gene transfer. Culture supernatant was tested in a marker rescue assay for replicationcom petent retrovirus (Allan et al, 1996). The remaining cells were either cryopreserved or infused directly.…”
Section: Marrow Cultures and Transduction Smentioning
confidence: 99%
“…LCa IDSN and LN supernatants were produced by the PA317 retroviral packaging cell line (Miller and Buttimore, 1986), and M48a ID was produced by the C CRIP retroviral packaging cell line (Danos and Mulligan, 1988). To ensure the absence of replication-comp etent retrovirus, supernatants from producer cell lines were routinely assayed by a sensitive marker rescue assay (Allan et al, 1996).…”
Section: Retroviral Vectorsmentioning
confidence: 99%
“…Many mouse strains constitutively express proteins of retroviral origin, and these proteins can be detected in CM [50,51]. Although Amit et al [52] reported that hESC maintained with mouse feeder cells are not infected with mouse viruses, it is known that under certain circumstances latent viruses can be spontaneously activated in cells that previously tested negative for infectious virus [53]. Thus we cannot completely rule out the possibility that retroviral Gag protein originating from mouse feeder cells is indicative of the production of active virus.…”
Section: Discussionmentioning
confidence: 97%
“…The infection potential of hightiter clones and proviral a-ID expression were confirmed by transduction of MPSI canine kidney cells. To ensure the absence of replication-competent retrovirus, supernatants from producer cell lines were assessed by a sensitive marker rescue assay (Allan et al, 1996). Two PG-13 clones, A12 and C6, were used for all further studies.…”
Section: Producer Cell Line Productionmentioning
confidence: 99%